2017
DOI: 10.3390/molecules22071225
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chlorhexidine-Encapsulated Mesoporous Silica Nanoparticles on the Anti-Biofilm and Mechanical Properties of Glass Ionomer Cement

Abstract: One of the primary causes for the failure of glass ionomer cement (GIC) is secondary caries. To enhance the anti-microbial performance of GIC without affecting its mechanical properties, chlorhexidine (CHX) was encapsulated in expanded-pore mesoporous silica nanoparticles (pMSN) to synthesize CHX@pMSN. CHX@pMSN was added at three mass fractions (1%, 5%, and 10% (w/w)) to GIC powder as the experimental groups. Pure GIC was set as the control group. The mechanical and anti-biofilm properties of GIC from each gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 42 publications
2
40
0
Order By: Relevance
“…The results of our study were in accordance with Huiyi Yan et al [37] who tested the antibacterial effect of the Glass Ionomer -Chlorhexidine mixture and concluded that CHX was continuously released, and antibiofilm ability was maintained up to 30 days.…”
Section: Chlorhexidinesupporting
confidence: 91%
“…The results of our study were in accordance with Huiyi Yan et al [37] who tested the antibacterial effect of the Glass Ionomer -Chlorhexidine mixture and concluded that CHX was continuously released, and antibiofilm ability was maintained up to 30 days.…”
Section: Chlorhexidinesupporting
confidence: 91%
“…Supplementation with these CHX salts has also been found to be associated with a negative impact on mechanical properties [6] , [10] , [11] , [12] . More recently, some attempts have been made to incorporate CHX when loaded into particles that may facilitate gradual rather than rapid release, and there has been some success in this, but still the CHX release was heavily front loaded and decayed rapidly after the first 1–3 days [13] .…”
Section: Introductionmentioning
confidence: 99%
“…However, it is necessary that further research should deal with more favorable incorporation approaches for endowing GIC with inuential anti-microbial capability and higher mechanical functions. 111 Maghsoudi et al examined the anti-biolm activity of nanosized curcumin-loaded particles synthesized by desolvation technique. Nano-particle systems have been explored in terms of the properties against Streptococcus mutans functions on dental models when curcumin was applied as a biological antibacterial factor to load into NPs.…”
Section: Dental Applications Of Nanomaterialsmentioning
confidence: 99%